Collaborative Governance in Management of the JakLingko Program (Case Study on Public Transportation Management in DKI Jakarta) - Rahma, Hanifa Aulia; Rosyadi, Slamet; Gunarto, Guntur; Simin (Indonesian Journal Publisher, 2024)
High population density and mobility in Jakarta have triggered persistent traffic congestion. The impacts are not only on time and cost but also on deteriorating air quality. Government efforts to provide alternative public transportation have not been fully effective, due to low public interest caused by inadequate facilities and limited accessibility. The solution is evident in the JakLingko Program, an initiative that integrates the public transportation system. To ensure the success of this program, the Jakarta Transportation Agency collaborates with public transportation modes and relevant businesses. Through this synergy, it is expected that public interest in using public transportation will increase, reducing the use of private vehicles, thereby alleviating traffic congestion and improving air quality in Jakarta. This research employs the collaborative governance model proposed by Ansell and Gash, encompassing four dimensions: initial conditions, institutional design, facilitative leadership, and collaboration processes. The research methodology is qualitative-descriptive. The research results indicate that collaborative governance in managing the JakLingko Program in Jakarta is fairly optimal, but not yet fully so.